Plan de marketing para la ferreteria “El Ferretero” del cantón Shushufindi, Provincia de Sucumbios, para el año 2017 - Sánchez Espinoza, Elías Humberto (2017)
This investigation has as main objective to indicate how the "Marketing Plan for the Hardware" was elaborated "El Ferretero" of the Shushufindi Canton, Province of Sucumbios ", for the year 2017 with the purpose to better satisfy its customers and that the Owners have a higher profitability. The objectives that were raised in this research are related to the external and internal analysis in order to determine the MATRIX FODA. For this project a marketing plan for the "El Ferretero" Hardware was elaborated, taking into consideration the surveys applied to the clients and employees; The owner of the hardware store was interviewed. With all the data obtained, the internal and external factors of the hardware store El Ferretero de Provincia de Sucumbíos were known based on the MATRIZ FODA. In the first place the methodology that was used, within the investigation and that was applied was the deductive method that helped to make an external analysis. On the other hand the inductive method that helped to obtain all the necessary information about the company. The synthetic method helped synthesize all the information obtained. The statistical method consists of a series of procedures for the management of the qualitative and quantitative data of the investigation. And the analytical method allowed to establish the mechanisms for the proposal of the marketing plan. The techniques used were (interview, survey, direct observation). The interview was addressed to Mr. Marcelo Rene Calvache Carrasco owner of the hardware store "El Ferretero" the surveys were made to both employees and customers, another technique that was used to find information about the environment of the company Was the direct observation, helping to verify personally, how the issue of marketing within the company is handled, which facilitated the collection of data on the current competition of the organization. Within the results the external analysis was performed, in the table of the Matrix of evaluation of the External Factors, once assigned the weighting for each of the external factors that influence the company the FERRETRO, we obtained the weighted result of 2, 71. The results were added. The total weighted value can not be greater than The weighted average value is 2.71. A May-2.5 total weighted value indicates that the company responds well to opportunities and threats, while a weighted value less than 2.5 indicates that opportunities are not being taken advantage of and threats can do much harm. The weighted total is 2.71, which indicates that the company is not taking advantage of some opportunities and that threats can harm it if it does not potentiate opportunities. According to the result obtained from the Matrix of Evaluation of internal factors of the company the FERRETRO, determines as a weighted result of 2.67; Means that in the company there is a predominance of strengths over weaknesses; Therefore the company, does not have internal problems that can interfere in the growth of the same and also that has a normal development within the local market. Through the High Impact Matrix, four strategic objectives were set out, among which we have: Structure and maintain a portfolio of clients or database, Expand participation in the company market through promotion and publicity, demonstrating quality Of its products, Achieve customer loyalty through its satisfaction and complacency and Improve customer service through the structure of a training plan for employees of the "EL FERRETERO" Hardware, these objectives with a value Of $ 6,373.60 for compliance. Finally, we have come to determine the conclusions and recommendations based on the market study and the proposal the recommendations that should be made in front of the implementation of the Marketing Plan.